Spermidine improves seed viability in Allium mongolicum by regulating AmCS-mediated metabolic and antioxidant networks - Men, Yan; Wei, Pengchao; Zhang, Fenglan; Huang, Xiumei; Zhang, Dong; Feng, Rongji; He, Xueqin; Yang, Zhongren (Frontiers in Plant Science, 2025)
IntroductionSeed deterioration involves oxidative damage and disrupted energy metabolism, yet the genetic mechanisms underlying aging resistance in Allium mongolicum remain unclear.MethodsIn this study, seeds primed with 0.8 mM spermidine (Spd) and stored for varying durations were subjected to transcriptome sequencing, targeted energy metabolite profiling, and assessments of antioxidant systems and energy metabolism enzymes.ResultsWe identified citrate synthase (AmCS) as a pivotal candidate gene involved in delaying aging processes. Under standard growth conditions, AmCS-overexpressing Arabidopsis lines exhibited a 15.55% higher germination rate compared to wild-type (WT), with enhanced activities of superoxide dismutase (SOD) and peroxidase (POD), and a 46.37% increase in ATP content compared to WT. Furthermore, these transgenic lines displayed significant reductions in hydrogen peroxide (H2O2; 35.20%) and malondialdehyde (MDA; 40.40%) accumulation. Mechanistically, AmCS-overexpressing Arabidopsis lines demonstrated heightened mitochondrial functionality, manifested as a 50.26% increase in cellular respiration rate and a 1.41-fold higher NADPH/NADP+ ratio than WT. Yeast two-hybrid assays validated the physical interaction between AmCS and pyruvate dehydrogenase kinase (AmPDK).DiscussionWe demonstrate that the AmCS-AmPDK complex retards seed aging through two key mechanisms: (i) promoting acetyl-CoA flux in the tricarboxylic acid (TCA) cycle and (ii) enhancing NADPH-dependent antioxidant capacity through pentose phosphate pathway activation. Exogenous Spd activates this network by inducing AmCS expression. Our findings establish AmCS as a key genetic regulator for enhancing anti-aging traits in crop breeding, offering prospects for precision breeding and advancements in seed storage practices.